2021
DOI: 10.1002/slct.202101925
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Selective C−S Bond Cleavage of Thioethers to Access β‐Alkoxy Carbonyl Compounds

Abstract: A metal-free C(sp 3 )À S bond cleavage of β-alkylthio carbonyl compounds in the presence of Selectfluor is described. This novel strategy realizes the CÀ S bond cleavage and subsequent CÀ O bond formation, providing a facile and efficient method to construct different important β-alkoxy carbonyl compounds with moderate to good yields and good functional groups tolerance. Moreover, our mechanistic studies also prove that two different mechanisms including the oxidant and thionium ion intermediate pathway may ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The proposed mechanisms, as depicted in Scheme 6, are supported by previous reports and control experiments. [6][7][8][9][10][11] The initial reaction between 1 a and NBS produces the transient salt A, which can subsequently be converted into the crucial sulfoxide B, HBr, and succimide. The control experiment showed that sulfoxide B was formed, indicating that the NH group of 1 a could not form a four-membered ring after generating intermediate A through neighboring group participation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed mechanisms, as depicted in Scheme 6, are supported by previous reports and control experiments. [6][7][8][9][10][11] The initial reaction between 1 a and NBS produces the transient salt A, which can subsequently be converted into the crucial sulfoxide B, HBr, and succimide. The control experiment showed that sulfoxide B was formed, indicating that the NH group of 1 a could not form a four-membered ring after generating intermediate A through neighboring group participation.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfoxide B can be transformed into acrylamide C at an elevated temperature. [8,9] Subsequently, the desired product 2 a is generated from either sulfoxide B or acrylamide C in the presence of in-situ formed HBr (path a). On the other hand, when using substrate 1 p, the initial transient salt D quickly converts into transient salts E, which can be further transformed into the final product 2 p along with byproduct 3 (path b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Moreover, halogenated reagents are also valuable in organic synthesis, and the following reagents are commonly used, including KF, Selectfluor, NFSI, NBS, NCS, NIS, I 2 , PhI(OAc) 2 , etc. 9–14 Wei's review 6 d outlined a transition-metal-free rearrangement reaction of thioethers with ortho -silylaryl triflates in the presence of KF or CsF. 9 The in situ formed arynes from ortho -silylaryl triflates react with thioethers to yield sulfonium intermediates, which is followed by subsequent C–S bond cleavage and transformations.…”
Section: C–s Bond Cleavage In Thioethersmentioning
confidence: 99%
“…[ 62 ] Ke Yang's group reported that in CS bond cleavage of thioethers (e.g., 3‐(methylthio)‐N‐phenylpropanamide), the CS bond with the lower bond energy was broken and the yield was 87%. [ 63 ] Furthermore, weak CS bond is easily cleaved in polar solvents through a nucleophilic attack on the positively disposed carbon center, which is followed by cleavage of the CS bond. [ 64 ] To our knowledge, dl ‐Methionine could be directly selected as control agent for RDRP has not been investigated.…”
Section: Introductionmentioning
confidence: 99%